Numerical simulations of different configured venous anastomosis in microvascular flap transfer. Issue 5 (May 2019) - Wittenborn, Julian; Büsen, Martin; Liao, Sam; Bartella, Alexander; Teichmann, Jan; Kamal, Mohammad; Hölzle, Frank; Lethaus, Bernd
Abstract: Background: Free flap surgery is a well-established method for covering large defects in the head and neck region. Most cases of flap failure are caused by venous thrombosis. Thus, there is a lot of discussion about the ideal design of venous anastomosis and its impact on the hemodynamics in the vessels. This study concentrates on the simulation of flow patterns of different designs of venous anastomoses. Methods: First, fluid flow rates were measured using transit-time flow measurement in the veins of 20 patients who received free flaps between 2016 and 2017. Five different designs of porcine anastomoses were scanned using micro-computed tomography, to create three-dimensional models. In the second step, numerical simulations of the blood flow were performed to gain insights into the vessel flow patterns. Results: The simulations revealed recirculation areas in the 60° and 90° end-to-side anastomoses, especially in combination with low fluid flow rates. In addition, there were large areas of recirculation in the 1:3 end-to-end anastomoses. Conclusion: The type of venous anastomosis should be decided individually. End-to-side anastomosis can be recommended in cases with high caliber differences or in those with high venous outflow. End-to-end anastomoses should be preferred in conditions with low venous outflow.